Creating Spiritual Value: The Islamic Way to Integrate Environmental and Social Responsibilities - Fidiana; Handayani, Nur; Retnani, Endang Dwi (Accounting Department,, 2022)
Purpose — While previous social and environmental accountability (SEA) research has been focused on company scenarios, in non-profit organizations (NPO), SEA has received little attention. This study focuses on traditional Islamic organizations as NPOs that provide commodities and services with the goal of increasing social value for the community at large. Accordingly, the current study aimed to develop a theoretical framework by elaborating the value system of main Islamic teachings to highlight the spiritual value of social and environmental consciousness and action. Design/methodology/approach — By employing the phenomenology approach through a way of interviews with several leaders as key persons in Al-Huda, this study found four major contributions were added to the existing literature. Findings — First, the belief in tauhid (Islamic monotheism) is the most fundamental aspect of the emotional spirit of social and environmental behavior. Second, the analysis shows that social and environmental responsibility was attached to personal responsibility. Third, the social and environmental responsibilities were aimed mostly at protecting the Islamic faith (aqidah). Fourth, analysis shows that accountabilities were for management and public purposes (horizontally) and for worship aspects (vertically). Practical implications — This case study emphasizes forms of social and environmental responsibility specific to Islamic entities, which may not be true in other entities. Originality/value — It shifts extrinsic goals such as economic motivation, profit, and business reputation in social and environmental activities into intrinsic and inherent moral responsibility. Keywords — Social and Environmental Sustainability; Tauhid; Worship; Holistic. Paper type — Case study